Community Pharmacy Practice in India: Past, Present and Future: Evolution and Future Prospects of Community Pharmacy Practice in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today, community pharmacists play an important role in any country as they take responsibility for patient’s medicine related needs for access to healthcare. However, in India only the supply of medicines remains the core activity of the community pharmacist. Most community pharmacists in the country still hardly offer patient-oriented service. The role of the pharmacists in the community, and with it their medicine management, may change in the wake of the rapid growth of domestic medicine output and national healthcare expenditure. This article seeks to discuss the genesis of Indian community pharmacy, the majority of which are privately owned, and sketches its education, training and future prospects. Pharmacy education continues to evolve to better prepare pharmacists for their roles and responsibilities in an increasingly complex health care environment with advanced patient health needs. Another important factor is the pharmacists themselves. Over the past 50 years, the role of pharmacists has evolved along with the health care needs of our population. In addition to dispensing medications and ensuring patient safety, today’s pharmacists are taking a larger role as medical counselors, educators and advocates. They are integral part of the health care team, and are among the most trusted and accessible health care professionals. This accessibility allows them to perform more patient care activities, including counseling, medication management, and preventive care screenings. Beyond the care provided to individual patients, pharmacists have expanded their reach to influence the public health of communities. All people who take medications are at risk of actual or potential drug therapy problems. These problems are a significant source of morbidity and mortality when left undetected and unresolved and drive huge costs across the health system. As drug therapy experts, pharmacists provide drug therapy management services built around a partnership between the pharmacist, the patient (or his or her caregiver), physicians and other members of a patient’s health care team.